Upregulation of miR‐874‐3p and miR‐874‐5p inhibits epithelial ovarian cancer malignancy via SIK2. Issue 8 (13th July 2018) - Xia, Bairong; Lin, Mei; Dong, Wei; Chen, Hong; Li, Bing; Zhang, Xiaye; Hou, Yan; Lou, Ge
Abstract: Based on miR‐874 expression levels in the GSE47841 microarray, we hypothesized that the mature products of miR‐874, miR‐874‐3p, or miR‐874‐5p, would inhibit epithelial ovarian cancer (EOC) cell proliferation, metastasis, and chemoresistance. We first examined miR‐874‐3p and miR‐874‐5p expression levels in primary EOC tumor tissue samples and found that they were significantly decreased. 3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide (MTT) cell proliferation and transwell assays revealed that miR‐874‐3p and miR‐874‐5p significantly inhibit EOC cell proliferation, migration, and invasion. Then, using MTT and soft agar assays of paclitaxel‐treated Caov3 and SKOV3 cells transfected with miR‐874‐3p and miR‐874‐5p, we found that miR‐874‐3p and miR‐874‐5p enhance EOC cell chemosensitivity. We then confirmed that serine/threonine‐protein kinase 2 (SIK2) was a target gene of miR‐874‐3p and miR‐874‐5p. Overall, the results of this study indicate that SIK2 expression can serve as a prognostic biomarker for EOC and that miR‐874‐3p and miR‐874‐5p have the potential to enhance clinical treatment of EOC.